2021
DOI: 10.1080/20002297.2021.1920226
|View full text |Cite
|
Sign up to set email alerts
|

Salivette, a relevant saliva sampling device for SARS-CoV-2 detection

Abstract: Background: The gold standard for COVID-19 diagnosis relies on quantitative reverse-transcriptase polymerase-chain reaction (RT-qPCR) from nasopharyngeal swab (NPS) specimens, but NPSs present several limitations. The simplicity, low invasive and possibility of self-collection of saliva imposed these specimens as a relevant alternative for SARS-CoV-2 detection. However, the discrepancy of saliva test results compared to NPSs made of its use controversial. Here, we assessed Salivettes®, as a standard… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 68 publications
(84 reference statements)
3
23
1
Order By: Relevance
“…Salivette ® cotton rolls were prepared as previously described [15]. If the retrieved saliva volume, after centrifugation, was less than 150 µL, 500 µL of ultra-pure water were loaded at the top of the cotton roll and the Salivette ® was then once again centrifuged at 1500× g for 2 min at 4 • C. The addition of ultra-pure water was done to 25 saliva samples.…”
Section: Saliva Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Salivette ® cotton rolls were prepared as previously described [15]. If the retrieved saliva volume, after centrifugation, was less than 150 µL, 500 µL of ultra-pure water were loaded at the top of the cotton roll and the Salivette ® was then once again centrifuged at 1500× g for 2 min at 4 • C. The addition of ultra-pure water was done to 25 saliva samples.…”
Section: Saliva Sample Preparationmentioning
confidence: 99%
“…In a previous study, we demonstrated the performance of a new saliva collection system, consisting in roll cotton and called Salivette ® (Neutral Salivettes ® , SARSTEDT, Numbrecht, Germany) as a homogeneous saliva collection system to diagnose COVID-19 by RT-qPCR [15]. The same protocol applied for SARS-CoV-2 diagnosis in a previous study [15] revealed a significantly higher sensitivity for SARS-CoV-2 detection in saliva collected with Salivettes compared to NPS. The only difference between this previous study and the present one was the realization of mouth washing prior to saliva collection.…”
Section: Introductionmentioning
confidence: 97%
“…Here, a larger series yielded results in less than 10 min and sensitivity was 96.7% when buccal sampling was supervised, compared to 60.7% when buccal sampling was not supervised. In fact, two min were required to appropriately collect saliva and mucosal buccal material [ 16 ]; a duration which could not be ensured in non-supervised procedure. Our interpretation is that standardization of the sample; and its supervision by trained personal, are the keys to success.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, isothermal amplification applied to saliva samples has also proved promising on a limited series of COVID-19 patients [ 15 ]. Moreover, it was recently demonstrated that saliva collection with a roll cotton improved significantly the molecular detection of SARS-CoV-2 compared to nasopharyngeal swab (NPS) specimens [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high concordance rate in the detection of respiratory viruses using molecular assays [15] between saliva and nasopharyngeal samples, including coronaviruses, has been demonstrated [16]. Although the clinical diagnosis of Coronavirus Disease 2019 (COVID-19) using saliva samples remains controversial, the comparison of nasopharyngeal and saliva paired-samples showed that SARS-CoV-2 was detected equivalently or better in saliva [17][18][19]. The identification of SARS-CoV-2 proteins in gargle solutions from patients with COVID-19 infection by a MS-method confirmed the local presence of viral proteins [20].…”
Section: Introductionmentioning
confidence: 99%